2011
DOI: 10.1080/02786826.2010.533215
|View full text |Cite
|
Sign up to set email alerts
|

Consistency and Traceability of Black Carbon Measurements Made by Laser-Induced Incandescence, Thermal-Optical Transmittance, and Filter-Based Photo-Absorption Techniques

Abstract: In this study, we show that black carbon (BC) mass concentrations measured by different techniques are consistent and traceable. First, we present the volatilities of 13 organic compounds passed through a heated inlet. These data were used to quantify the interference of organic aerosols on the BC measurement techniques. The masses of the refractory particles that incandesce (m * ref ) were used to calibrate BC mass measured by a single-particle soot photometer (SP2), which uses laser-induced incandescence. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
288
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 203 publications
(303 citation statements)
references
References 51 publications
15
288
0
Order By: Relevance
“…31,57,58 In general there has been agreement among those measurements, with the exception of a recent study 59 which showed a 30−40% low bias for thermal−optical techniques relative to the SP2. However, none of those comparisons utilized BC particles from gasoline engines, or they were performed in areas dominated by diesel emissions, away from direct sources, and with observed ambient mass mode diameters >150 nm.…”
Section: Resultsmentioning
confidence: 84%
“…31,57,58 In general there has been agreement among those measurements, with the exception of a recent study 59 which showed a 30−40% low bias for thermal−optical techniques relative to the SP2. However, none of those comparisons utilized BC particles from gasoline engines, or they were performed in areas dominated by diesel emissions, away from direct sources, and with observed ambient mass mode diameters >150 nm.…”
Section: Resultsmentioning
confidence: 84%
“…Although BC brings to mind a material, and many aerosol papers refer to it as if it were a specific material, laboratory samples of atmospheric BC that can be measured do not exist. In the absence of an accepted BC standard, surrogate materials such as fullerene, graphite, and Aquadag are used as standards (Gysel et al 2011;Kondo et al 2011;Baumgardner et al 2012;Laborde et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Kondo et al (2011b) also reported that when performing BC measurements via other techniques, the use of a 300…”
Section: Introductionmentioning
confidence: 99%
“…The peak of the LII intensity can be used to quantify the mass of BC aerosol on a per-particle basis after calibration (Kondo et al 2011b). The calibration of the SP2 system is typically achieved using commercially available size or mass-selected BC particles of known density (Baumgarder et al 2004), with similar refractive index and particle shape to that of ambient BC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation